VARIASI DIAMETER SPRING MENGGUNAKAN NACA 0015 SEBAGAI SISTEM DAYA DORONG - Andi Wibisono (2023)
The impact of increasingly advanced climate change has a detrimental impact on gas emissions, especially in the shipping sector, this requires us to reduce the greenhouse effect. There are several systems of ways to utilize energy, alternative energy being developed is wave energy which can be used to propel ships. Referring to Prof.'s research. Kenichi Horie proved that ocean waves and currents can be a driving force for ships by driving NACA. In this study the focus is on calculating the lift force from a NACA, followed by calculating the frequency generated by the spring system and finally calculating the thrust generated by the system. Starting with spring system modeling and NACA 0015. NACA lift force calculations will be carried out using Ansys Fluent Software, variations in spring diameter, modifying Wire Diameter by 0.9, 1.0, 1.1, 1.2 Inch and speed of 5, 10, 15, 20, 25, 30, Knots using NACA 0015 as the ship's propulsion system. This analysis uses Computational Fluid Dynamics (CFD) and Finite Element Method (FEM) approaches. Based on the simulation results that have been carried out, it shows that the most optimal variation of the spring system is at L1W1, 2N5 with a frequency value of 7.9793 Hz at a speed of 30 Knots.